Global Economic Policy Uncertainty and Investment Efficiency : Evidence from Emerging Country - Mubashir, Ali Khan; Josephine Tan Hwang, Yau (Human Resource Management Academic Research Society, 2023)
The aim of this study is to examine the relationship between global economic policy uncertainty and investment efficiency. A global measure of economic policy uncertainty was used in this paper by collecting the data over the period 2010-2022 to create a sample of 10,130 observation years using the OLS regression method. This paper finds that investment inefficiency increases when global policy uncertainty increases. It also highlights that firms’ characteristics have a significant influence on investment efficiency as compared to macroeconomic factors. The findings of this study guides investors, governments and policy makers needs to consider global economic policy when changing and guiding policies related to efficient allocation of capital.